Therapeutic potential of β-arrestin- and G protein-biased agonists - Whalen, Erin J. (2010)
Members of the seven-transmembrane receptor (7TMR), or G protein-coupled receptor (GPCR), superfamily represent some of the most successful targets of modern drug therapy, with proven efficacy in the treatment of a broad range of human conditions and disease processes. It is now appreciated that β-arrestins, once viewed simply as negative regulators of traditional 7TMR-stimulated G protein signaling, act as multifunctional adapter proteins that regulate 7TMR desensitization and trafficking and promote distinct intracellular signals in their own right. Moreover, several 7TMR biased agonists, which selectively activate these divergent signaling pathways, have been identified. Here we highlight the diversity of G protein- and β-arrestin-mediated functions and the therapeutic potential of selective targeting of these in disease states.